UV-MALDI-TOF Mass Spectrometry Analysis of Heparin Oligosaccharides Obtained by Nitrous Acid Controlled Degradation and High Performance Anion Exchange Chromatography - Bultel, L. (2010)
Nitrous acid degradation of heparin followed by high-performance anion-exchange chromatography (HPAEC) separation and ultraviolet matrix assisted laser desorption/ionization time-of-flight (UV-MALDI-TOF) analysis led to the structural determination of six sulfated oligosaccharides. Three different matrices (α-cyano-4-hydroxycinnamic acid (CHCA), nor-harmane, and dihydroxybenzoic acid (DHB)) have been used, and the complementary results obtained allowed in most cases to assign the position of sulfate groups. Based on the different cleavages produced on the purified oligosaccharides in source during the MS analysis by the use of the different matrices, this approach provides a new tool for structural analysis. © 2010 American Society for Mass Spectrometry.